2022
DOI: 10.1007/s42250-022-00409-1
|View full text |Cite
|
Sign up to set email alerts
|

Phenolic Compounds Profile from Algerian Pomegranate Fruit Extract (Punica Granatum L.) by UPLC-DAD-ESI-MS

Abstract: with details of the nature of the infringement. We will investigate the claim and if justified, we will take the appropriate steps.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
4
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 40 publications
1
4
0
Order By: Relevance
“…Our results have indicated that hydroalcoholic fruits peels extract of pomegranate (Punica granatum L.) has significantly (p˂0.0001) a higher TPC, TF and TFL values than fruits peels extract of Opuntia ficus indica L. The highest TPC, TF and TFL were obtained for hydroalcoholic fruits peels extract of pomegranate (Punica granatum L.) (590.07±13.58 mg/g GAE g 1-, 227.85± 46.48 mg/g QE g 1-, 91.57±5.79 mg/g QE g 1-, respectively) (Table 1). The current results show that main compounds are flavonoids and flavonol derivatives in the extracts of pomegranate fruits peels, which is in agreement with findings of studies performed previously [24][25][26] . It is further reported that level of phenolic compounds is changed with fruits parts and their cultivars as discussed by Sushil Belkacem et al 22 ; Linlin et al 23 and Kumar Middha et al 27 .The peel extract contained the highest level of total phenolic content that were obtained in all cultivars.…”
Section: Antioxidant Activitysupporting
confidence: 93%
“…Our results have indicated that hydroalcoholic fruits peels extract of pomegranate (Punica granatum L.) has significantly (p˂0.0001) a higher TPC, TF and TFL values than fruits peels extract of Opuntia ficus indica L. The highest TPC, TF and TFL were obtained for hydroalcoholic fruits peels extract of pomegranate (Punica granatum L.) (590.07±13.58 mg/g GAE g 1-, 227.85± 46.48 mg/g QE g 1-, 91.57±5.79 mg/g QE g 1-, respectively) (Table 1). The current results show that main compounds are flavonoids and flavonol derivatives in the extracts of pomegranate fruits peels, which is in agreement with findings of studies performed previously [24][25][26] . It is further reported that level of phenolic compounds is changed with fruits parts and their cultivars as discussed by Sushil Belkacem et al 22 ; Linlin et al 23 and Kumar Middha et al 27 .The peel extract contained the highest level of total phenolic content that were obtained in all cultivars.…”
Section: Antioxidant Activitysupporting
confidence: 93%
“…Moreover, the preliminary phytochemical investigation on the fruit extracts of V. vinifera and P. granatum demonstrated that V. vinifera and P. granatum are a rich source of phenolic compounds, including gallic acid, catechins and resveratrol, as well as a wide range of procyanidins [9,19] which can accelerate wound healing. The presence of these metabolites, which are reported to play a critical role in the wound healing process by increasing the rate of wound contraction, lowering the period of epithelialization and preventing secondary bacterial infections that would induce complex and delayed wound healing, could explain the wound healing activity [29,30].…”
Section: Discussionmentioning
confidence: 99%
“…The lyophilized edible fruits were subjected to extraction by maceration assisted by ultrasound [9,19] in an ultrasonic bath (Fisher scientific fb 15046, Leicestershire, England) (>20 kHz in frequency) for 30 min at room temperature using methanol/water (70/30) as solvent in a solid/liquid ratio of 25 g/500 ml, followed by maceration in a magnetic stirrer for 24h. The remaining vegetal material was extracted again twice under identical conditions.…”
Section: Extraction Processmentioning
confidence: 99%
“…21 A recent study on Algerian pomegranate fruit identified more than 50 phenolic compounds, including many substances that were detected for the first time in the pomegranate fruit extract. 22 Akhtar et al 23 mentioned that the properties of pomegranate are not limited to the edible part of the fruit but also to the non-edible part such as peels, even though they are considered waste. According to previous reports, the pomegranate peels are rich in chemical compounds including phenolic acids (e.g.…”
Section: Introductionmentioning
confidence: 99%